Surgical versus injection treatment for injection-confirmed chronic sacroiliac joint pain - Spiker, William Ryan; Lawrence, Brandon D; Raich, Annie L; Skelly, Andrea C; Brodke, Darrel S (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Study rationale: Chronic sacroiliac joint pain (CSJP) is a common clinical entity with highly controversial treatment options. A recent systematic review compared surgery with denervation, but the current systematic review compares outcomes of surgical intervention with therapeutic injection for the treatment of CSJP and serves as the next step for evaluating current evidence on the comparative effectiveness of treatments for non-traumatic sacroiliac joint pain. Objective or clinical question: In adult patients with injection-confirmed CSJP, does surgical treatment lead to better outcomes and fewer complications than injection therapy? Methods: A systematic review of the English-language literature was undertaken for articles published between 1970 and June 2012. Electronic databases and reference lists of key articles were searched to identify studies evaluating surgery or injection treatment for injection-confirmed CSJP. Studies involving traumatic onset or non-injection–confirmed CSJP were excluded. Two independent reviewers assessed the level of evidence quality using the grading of recommendations assessment, development and evaluation (GRADE) system, and disagreements were resolved by consensus.Results: We identified twelve articles (seven surgical and five injection treatment) meeting our inclusion criteria. Regardless of the type of treatment, most studies reported over 40% improvement in pain as measured by Visual Analog Scale or Numeric rating Scale score. Regardless of the type of treatment, most studies reported over 20% improvement in functionality. Most complications were reported in the surgical studies.Conclusion: Surgical fusion and therapeutic injections can likely provide pain relief, improve quality of life, and improve work status. The comparative effectiveness of these interventions cannot be evaluated with the current literature.